Development And Validation Of Next-Generation Learning Materials For Customary Law In Open Distance Education - Sardjiyo (ASIAN PUBLISHER, 2026)
Next-generation learning materials (BP-GERU UT) represent a strategic initiative by Universitas Terbuka (UT) to develop multi-modal instructional resources capable of supporting conventional, blended, and fully online learning environments across Indonesia’s geographically diverse student population. This study reports the third phase of a multi-year Research and Development (R&D) project focused on the validation, field testing, and dissemination of the BP-GERU UT prototype for the Customary Law course in the Pancasila and Civic Education (PPKn) program. Employing Gall et al. (2007) R&D framework, the study covered Steps 9–15 of the development cycle, encompassing expert validation through Focus Group Discussions, micro-scale field testing involving 346 students across 15 regional learning centers, and macro-scale operational testing involving 670 students across 20 regional centers with varying levels of internet connectivity. Expert validation yielded substantive recommendations for content breadth, language clarity, and visual design. Micro-scale testing demonstrated a 2.84% improvement in pre-test to post-test performance, while macro-scale testing revealed an average gain of 4.06% (pre-test mean: 76.91; post-test mean: 80.03). Regions with good internet access (Zone A) showed the highest improvement (4.76%), followed by moderate-access (Zone B, 4.43%) and limited-access regions (Zone C, 3.19%). These findings confirm that the BP-GERU UT prototype is effective across diverse delivery contexts and suitable for national-scale implementation in open distance education.